2022
DOI: 10.3390/gels8080524
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Based Edible Gels as Functional Ingredients: Characterization, Applicability, and Human Health Benefits

Abstract: Nowadays, edible materials such as polysaccharides have gained attention due to their valuable attributes, especially gelling property. Polysaccharide-based edible gels (PEGs) can be classified as (i) hydrogels, (ii) oleogels and bigels, (iii) and aerogels, cryogels and xerogels, respectively. PEGs have different characteristics and benefits depending on the functional groups of polysaccharide chains (e.g., carboxylic, sulphonic, amino, methoxyl) and on the preparation method. However, PEGs are found in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 170 publications
0
14
0
Order By: Relevance
“…Chitosan oligosaccharide (COS) is derived by the hydrolysis and deacetylation of chitin, a polymer of N-acetyl-D-glucosamine, which is a main constituent of the exoskeleton of arthropods such as insects, crabs and shrimps, and the cell wall of fungi [ 15 , 16 , 17 , 18 , 19 ]. The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ]. Due to its favorable pharmacokinetics and beneficial biological activities including anti-oxidative, anti-inflammatory, anti-diabetic, anti-bacterial, and anti-cancer activities, COS has the potential for development as dietary supplements or nutraceuticals [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan oligosaccharide (COS) is derived by the hydrolysis and deacetylation of chitin, a polymer of N-acetyl-D-glucosamine, which is a main constituent of the exoskeleton of arthropods such as insects, crabs and shrimps, and the cell wall of fungi [ 15 , 16 , 17 , 18 , 19 ]. The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ]. Due to its favorable pharmacokinetics and beneficial biological activities including anti-oxidative, anti-inflammatory, anti-diabetic, anti-bacterial, and anti-cancer activities, COS has the potential for development as dietary supplements or nutraceuticals [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ]. Due to its favorable pharmacokinetics and beneficial biological activities including anti-oxidative, anti-inflammatory, anti-diabetic, anti-bacterial, and anti-cancer activities, COS has the potential for development as dietary supplements or nutraceuticals [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previously, we have reported that COS activated AMP-activated protein kinase (AMPK) in the intestinal epithelial cells via a mechanism involving calcium sensing receptor (CaSR)-mediated calcium release from the endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic is a flexible synthetic material formed from ethylene and a semi-crystalline high-molecular-weight polymer. Basic materials obtained from oil, coal, and natural gas are used to produce plastics [ 33 , 34 , 35 , 36 , 37 ]. Roughly 15.46 tons of plastic waste is processed in India every day, only 40% of which can be recycled, and the remaining 60% is impossible to dispose of, according to a 2003 survey.…”
Section: Plasticsmentioning
confidence: 99%
“…They can modulate the intestinal microbial population (limitation of pathogens proliferation; controlling commensal bacteria and probiotics; enhanced host-microorganisms interactions) with beneficial effects. [48] Polysaccharides ionogels and various other co-components, natural and/or synthetic Divalent metal cations based hydrogels for energy storage, sensing, biomedical and environmental applications.…”
Section: Polysaccharidesmentioning
confidence: 99%